The Signum Harpocraticum in the 8th-century Christian Art of Nubia - Eirini, Panou (Actual Problems of Theory and History of Art, 2015)
The Egyptian god Horus was known from the second millennium BC as “the child with a finger in his mouth”. Hieroglyphics show that the placement of fingers onto the lips pertains to the believer’s responsibility to stay silent in the presence of the divine out of respect. In Eastern Christianity, the ancient Egyptian prohibition of speaking when God is present – now effectuated in churches – was continued more prominently both in texts and less often iconography. In general, the significance of the gesture of silence is defined as the appropriate behaviour that the faithful should adopt when confronting god in their prayers or when entering religious spaces. However, textual and iconographical evidence shows that this particular gesture was multilayered and could be explained on a theological or philosophical level depending on the era and region it appears. This article explores the semiotics of the silence gesture for a female saint in the 8th-century Cathedral of Paul, in Faras, Nubia.
Keywords: St. Anne; silence; signum harpocraticum; Nubia